Strategi Organizational Development Melalui Aplikasi Persuratan dan Kearsipan Elektronik My Office di Universitas Negeri Yogyakarta - Herman Setyawan (Program Studi Kearsipan, DBSMB SV UGM, 2018)
Every organization is very necessary to develop along with the times. Organizations must be able to adapt to changes in various aspects of life, such as technological, economic, political, and cultural change. In facing change, a concept is needed to assist an organization in creating an effective response to this change. This paper is based on the development of My Office application of mailing and filing at Universitas Negeri Yogyakarta (UNY), especially in the Sub-Section of Administration and Filing as the key holder of the UNY Rectorate system, and then analyzed with the organizational development model developed by Kurt Lewin. With a qualitative-descriptive approach, this study attempts to answer the question: